2018
DOI: 10.1108/ijmf-09-2017-0200
|View full text |Cite
|
Sign up to set email alerts
|

The role of directors: unravelling the effects of boards on corporate outcomes

Abstract: Purpose The purpose of this paper is to analyse whether the theoretical relationship between the board composition and the cost of capital (CC) is mediated by risk disclosure (RD) practices. Design/methodology/approach Partial least squares techniques are used, and a sample of all the companies belonging to manufacturing industry listed on Standard and Poor’s 500 for the year 2009 is studied. In relation to board composition, several recommendations issued by US governance codes are considered: board indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The board serves the significant role of monitoring on behalf of shareholders, can affect corporate outcomes (Bravo et al, 2018;Stiles, 2001) and also serves as an advisory body which contributes resources and expertise otherwise absent in an organization (Baysinger and Butler, 1985;Dalton et al, 1999). Therefore, whether the origin of aversion toward M&A transactions is in type-II agency problems or it is on account of lack of expertise and resources, we hypothesize that certain characteristics of the board can help mitigate the aversion.…”
Section: Why Board Characteristics Might Affect Manda Decisions?mentioning
confidence: 99%
“…The board serves the significant role of monitoring on behalf of shareholders, can affect corporate outcomes (Bravo et al, 2018;Stiles, 2001) and also serves as an advisory body which contributes resources and expertise otherwise absent in an organization (Baysinger and Butler, 1985;Dalton et al, 1999). Therefore, whether the origin of aversion toward M&A transactions is in type-II agency problems or it is on account of lack of expertise and resources, we hypothesize that certain characteristics of the board can help mitigate the aversion.…”
Section: Why Board Characteristics Might Affect Manda Decisions?mentioning
confidence: 99%
“…For instance, the likelihood of corporate failure has been negatively associated with ownership concentration and state ownership (Li et al, 2008), with institutional ownership (Manzaneque et al, 2016b;Udin et al, 2017) and with board ownership (Abdullah, 2006). Although the majority of these studies have used corporate governance characteristics individually, the recent literature also calls for the need to employ composite measures, which aggregates a number of governance indicators considering the interaction between multiple corporate governance mechanisms, to provide a better overview of the effectiveness of corporate governance structures (Brown et al, 2011;Jain and Jamali, 2016;Bravo et al, 2018). Consistent with this approach, our paper focuses on aggregated measures about the compliance of CGC recommendations to examine the effects of corporate governance on firms` financial distress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, in addition to the effect of ethical reputation on value relevance produced by female presence on corporate boards, Bravo et al. (2018) argued that such presence reduces the cost of capital and increases value relevance. Focusing on manufacturing industries listed on Standard and Poor's 500 for 2009, they found that boards with a high female presence, following the governance code's recommendations, lead to a reduction in the cost of capital through the disclosure of information on risks.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The table should suggest that female presence is only one of the variables that might be included in the so-called other information and that studies on the relationship between female presence and value relevance have provided very limited evidence about its ability to affect the weight investors place on earnings and book value. Second, in addition to the effect of ethical reputation on value relevance produced by female presence on corporate boards, Bravo et al (2018) argued that such presence reduces the cost of capital and increases value relevance. Focusing on manufacturing industries listed on Standard and Poor's 500 for 2009, they found that boards with a high female presence, following the governance code's recommendations, lead to a reduction in the cost of capital through the disclosure of information on risks.…”
Section: Net Asset Value Per Share Is Value Relevant On Thementioning
confidence: 99%